Existence and estimation of the Hausdorff dimension of attractors for an epidemic model. (21st June 2016) - Anguiano, María
Abstract : We prove the existence of pullback and uniform attractors for the process associated to a non‐autonomous SIR model, with several types of non‐autonomous features. The Hausdorff dimension of the pullback attractor is also estimated. We illustrate some examples of pullback attractors by numerical simulations. Copyright © 2016 John Wiley & Sons, Ltd.